2017
DOI: 10.1159/000480418
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Sika Deer Antler Protein on Cisplatin-Induced Nephrotoxicity

Abstract: Background/Aims: This study measured the effect of Sika deer (Cervus nippon Temminck) antler protein (SDAPR), glycoproteins (SDAG), and polysaccharides (SDAPO) on cisplatin-induced cytotoxicity in HEK 293 cells, and investigated the effect of SDAPR against cisplatin-induced nephrotoxicity in mice. Methods: Cell viability was measured by MTT assay. ICR mice were randomly divided into five groups: control, cisplatin with vehicle, and cisplatin with SDAPR at three concentrations: 5, 10, or 20 mg/kg, p.o., 10 d. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It was reported that oxidative stress and inflammation are also leading factors in CDDP-induced nephrotoxicity [ 10 ]. As CDDP exposure causes renal dysfunction, accompanying oxygen-derived free radicals (ROS) lead to oxidative stress, such as excessive lipid peroxidation, which results in a response of numerous proinflammatory cytokines and inflicts irreversible cellular damage in the kidney [ 11 , 12 , 13 ]. Sirtuin-1 (Sirt-1) is an important protein that is involved in the biological processes of CDDP-induced oxidative stress and inflammation by activating transcriptional activity of downstream genes, including nuclear-related factor 2 (Nrf2) and nuclear factor-kappa B (NF-κB) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that oxidative stress and inflammation are also leading factors in CDDP-induced nephrotoxicity [ 10 ]. As CDDP exposure causes renal dysfunction, accompanying oxygen-derived free radicals (ROS) lead to oxidative stress, such as excessive lipid peroxidation, which results in a response of numerous proinflammatory cytokines and inflicts irreversible cellular damage in the kidney [ 11 , 12 , 13 ]. Sirtuin-1 (Sirt-1) is an important protein that is involved in the biological processes of CDDP-induced oxidative stress and inflammation by activating transcriptional activity of downstream genes, including nuclear-related factor 2 (Nrf2) and nuclear factor-kappa B (NF-κB) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found an effect which GM administration could significantly increase levels of serum BUN and Cr after GM injected [24][25][26]. Conversely, the higher BUN and Cr as an indicator of kidney dysfunction in GM-induced mice recovered to normal levels after co-treatment with SDAPR.…”
Section: Discussionmentioning
confidence: 79%
“…(1) Groups 1 (male, n � 6) and 8 injection, the combination of NS (12.5 ml kg, ip) and furosemide (F, 2.5 ml/kg, ip) was administrated. (4) Groups 5 (male, n � 6) and 12 (female, n � 6) are named M, NS + CP + NS.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Several studies have been done in order to assess the protective effect of different synthetic and herbal antioxidants supplements against CP-induced nephrotoxicity [7][8][9][10][11]. In addition, other studies have been tried to alleviate the adverse effect of CP-induced nephropathy [12][13][14].…”
Section: Introductionmentioning
confidence: 99%